Amanat tahun baharu Rektor 2025 / Saunah Zainon - Zainon, Saunah (UiTM Cawangan Johor, 2025)
The New Year Address delivered by the Rector outlines the institution's vision, achievements, and strategic direction for the upcoming year. The speech emphasizes key accomplishments from the past year, highlighting improvements in academic excellence, research output, student development, and institutional governance. It also underscores the challenges faced and the proactive measures taken to address them. The Rector articulates future aspirations, focusing on digital transformation, global collaboration, and sustainability in higher education. Furthermore, the address motivates faculty, staff, and students to embrace innovation, resilience, and a growth mindset. The speech concludes with an inspiring call for unity and collective effort in achieving the institution’s long-term goals.